2021
DOI: 10.1186/s12888-021-03618-z
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety severity and cognitive function in primary care patients with anxiety disorder: a cross-sectional study

Abstract: Background Deficits in cognitive performance are reported in patients with anxiety disorders, but research is limited and inconsistent. We aimed to investigate cross-sectional associations between cognitive function, with focus on executive function, and anxiety severity in primary care patients diagnosed with anxiety disorders. Methods 189 Swedish patients aged 18–65 years (31% men) with anxiety disorders diagnosed according to Mini International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…DSF is typically considered highly stable, with negligible practice effects [20] and not amenable to short-term intervention. Some variation in DSF scores was observed in response to state and trait anxiety [21] . Treatment effects, when observed, typically result from extensive training, either in the form of repetitive practice or the development of elaborate metacognitive strategies (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…DSF is typically considered highly stable, with negligible practice effects [20] and not amenable to short-term intervention. Some variation in DSF scores was observed in response to state and trait anxiety [21] . Treatment effects, when observed, typically result from extensive training, either in the form of repetitive practice or the development of elaborate metacognitive strategies (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Researchers have found that individuals suffering from depression exhibit changes in executive function [ 104 ], working memory [ 105 ], delayed memory [ 106 ], and attention [ 107 ]. Anxiety disorders have been characterized by similar cognitive deficits to working memory, delayed memory [ 106 ], executive function [ 108 ], processing speed, inhibition, and problem solving [ 109 ]. Such cognitive changes have also been observed for people experiencing loneliness [ 16, 52 ] and social isolation [ 16, 60 ].…”
Section: Associations Between Loneliness Social Isolation and Mental ...mentioning
confidence: 99%
“…Fourth , there may also be shared neuropsychological mediators. Deficient executive functions, common in ADHD (Willcutt, Doyle, Nigg, Pennington, & Pennington, 2005), are also observed in autism (Craig et al., 2016), depression (Fenesy & Lee, 2019), and anxiety (Nyberg et al., 2021), and they appear to drive its co‐occurrence with autism (Lukito et al., 2017) and depression (Fenesy & Lee, 2019) in particular. Developmentally, cognitive inflexibility is most prominent in young autistic children with other EF difficulties increasing with age, while inhibition problems are most prominent in young children with ADHD (Visser, Rommelse, Greven, & Buitelaar, 2016).…”
Section: Conceptualizing Correlated Characteristics and Co‐occurring ...mentioning
confidence: 99%